2016
DOI: 10.1038/pr.2016.139
|View full text |Cite
|
Sign up to set email alerts
|

Association of MBOAT7 gene variant with plasma ALT levels in children: the PANIC study

Abstract: Children carrying the T allele of the MBOAT7 polymorphism had higher plasma ALT than the noncarriers. Children with the MBOAT7, PNPLA3, and TM6SF2 variants had the highest plasma ALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 17 publications
1
45
0
1
Order By: Relevance
“…Luukkonen et al replicated effects of the MBOAT7 rs641738 variant on NAFLD with respect to steatosis, necroinflammation and fibrosis in 115 European adults. In a population sample of children from Finland, Viitasalo et al reported that subjects carrying the risk allele of the MBOAT7 polymorphism had higher ALT levels. These data suggest MBOAT7 is important in modulating the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Luukkonen et al replicated effects of the MBOAT7 rs641738 variant on NAFLD with respect to steatosis, necroinflammation and fibrosis in 115 European adults. In a population sample of children from Finland, Viitasalo et al reported that subjects carrying the risk allele of the MBOAT7 polymorphism had higher ALT levels. These data suggest MBOAT7 is important in modulating the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients carrying T allele show an enhanced intrahepatic TG content in these two independent cohorts and a higher prevalence of NASH and fibrosis in the LBC cohort, compared with non-carriers (60). Furthermore, children carrying the T allele of MBOAT7 have higher plasma ALT levels, C-reactive protein (CRP) concentration and body fat percentage than the non-carriers (62).…”
Section: The Mboat7 Rs641738 Variant Is Novel a Risk Factor For Nafldmentioning
confidence: 90%
“…Other candidate genes associated with NAFLD have been proposed, including a variant (rs641738) in the membrane bound O‐acyltransferase domain containing 7‐transmembrane channel‐like 4 ( MBOAT7 ) gene, which is associated with NAFLD in adults. Children carrying the minor allele of the MBOAT7 gene have higher ALT plasma levels compared to non carriers …”
Section: Genetic Variants Causing Nafld/nashmentioning
confidence: 99%